Las 5S en instituciones de educación básica regular en Perú - Noriega-Araníbar, María Teresa; Díaz-Garay, Bertha Haydeé; Berrocal Rodriguez, Lilian (Pontificia Universidad Católica del Perú, 2025)
This study aims to describe how the implementation of the 5S methodology contributes to the development of a quality culture in regular basic education institutions in Peru. A qualitative, non-experimental, and descriptive research design was employed, using semi-structured interviews conducted with informed consent. The sample consisted of four educational institutions, selected to explore perceptions regarding the benefits of implementation. The findings revealed a lack of formal planning in the implementation process, which was typically initiated by a teacher or principal and carried out with trained student leaders. Reported benefits include improvements in the classroom environment, communication spaces, waste reduction, and student performance—factors that collectively foster a culture of quality.

La investigación tiene como objetivo describir la manera cómo la aplicación de la metodología 5S contribuye a la formación de una cultura de calidad en entidades de educación básica regular en el Perú. La metodología empleada fue cualitativa, no experimental, con carácter descriptivo; se usó una entrevista semiestructurada con consentimiento informado. Se han considerado como muestra en el estudio cuatro entidades educativas para comprender la percepción sobre los beneficios de la implementación. Se observa la falta de una planificación para la implementación, siendo iniciativa de algún docente o director y llevándose a cabo con líderes escolares capacitados. Se resalta los beneficios en el ambiente de clases, espacios de comunicación, la reducción de desperdicios y mejora del desempeño del alumno, contribuyendo a la formación de una cultura de calidad.

Este estudo tem como objetivo descrever de que forma a aplicação da metodologia 5S contribui para o desenvolvimento de uma cultura de qualidade em instituições de educação básica regular no Peru. A pesquisa utilizou uma abordagem qualitativa, de natureza não experimental e caráter descritivo, com a realização de entrevistas semiestruturadas mediante consentimento informado. A amostra foi composta por quatro instituições educacionais, com o intuito de compreender as percepções sobre os benefícios da implementação. Observou-se a ausência de um planejamento estruturado, sendo a iniciativa geralmente conduzida por um professor ou diretor, com o apoio de líderes estudantis capacitados. Os benefícios destacados incluem melhorias no ambiente de sala de aula, nos espaços de comunicação, na redução de desperdícios e no desempenho dos alunos, contribuindo para o fortalecimento de uma cultura de qualidade.
The 5S Methodology in Regular Basic Education Institutions in Peru
A Metodologia 5S em Instituições de Educação Básica Regular no Peru
Keywords: School management; Continuous improvement; Decision-making; Organizational values; Gestión del centro de enseñanza; Mejora continua; Toma de decisiones; Valores organizacionales; Gestão escolar; Melhoria contínua; Tomada de decisão; Valores organizacionais; https://purl.org/pe-repo/ocde/ford#5.03.00